Separación y cuantificación de micotoxinas producidas por Fusarium spp. mediante UHPLC-DAD - Maldonado, Florencia N.; Gonzalez, Roxana Elizabeth; Bazterra, Delfina; Caligiore Gei, Pablo Fernando; Quintas, Pamela Y. (Universidad Nacional de San Juan, 2024)
Poster y resumen